Konstrukcja Skali Poczucia Umiejscowienia Kontroli Zdarzeń Szkolnych - Poziemska, Joanna (Kultura-Społeczeństwo-Edukacja, 2020)
Many studies have shown that the activity of individuals depends, among others, on constructs such as self-efficacy, self-esteem, motivation, learned helplessness or relations with the environment. They are in turn closely related to the locus of control. As it takes shape under the influence of experiences, past events are important in this process, for students – school events in particular must be taken into account. Due to the fact that tools are missing that could be used by paedagogues to study and diagnose the locus of control of school events in pupils, an attempt has been made to construct it. Existing tools are constructed in other cultures or socio-economic conditions, so this research is an attempt to construct a tool to determine the direction of explaining school events, separately for successes and failures. The sample consisted of 449 second graders from schools above the lower secondary level. The reliability of the tool was verified by the internal compliance coefficient and the validity – by studying the relationship with the chosen variables. The tool can be considered validated. In terms of the failures scale, the tool achieved satisfactory reliability, while the in terms of the scale of success – it needs more development